2008
DOI: 10.1152/ajpcell.00062.2008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell surface expression of functional pacemaker channels by a motif in the B-helix of the cyclic nucleotide-binding domain

Abstract: EA. Regulation of cell surface expression of functional pacemaker channels by a motif in the B-helix of the cyclic nucleotide-binding domain. Am J Physiol Cell Physiol 295: C642-C652, 2008. First published July 9, 2008 doi:10.1152/ajpcell.00062.2008.-Previous studies have suggested that a portion of the cyclic nucleotide-binding domain (CNBD) of the hyperpolarization-activated cyclic nucleotide-gated channel 2 (HCN2) "pacemaker" channel, composed of the A-and B-helices and the interceding ␤-barrel, confers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Recently, a four-amino acid motif (EEYP) in the B-helix of HCN2 was identified that strongly promotes channel export from the endoplasmatic reticulum and targeting to the cell membrane (287).…”
Section: B Pore Loop and Selectivity Filtermentioning
confidence: 99%
“…Recently, a four-amino acid motif (EEYP) in the B-helix of HCN2 was identified that strongly promotes channel export from the endoplasmatic reticulum and targeting to the cell membrane (287).…”
Section: B Pore Loop and Selectivity Filtermentioning
confidence: 99%
“…This system was chosen for two reasons: first, nonglycosylated Shaker, the prototypical channel in the Kv superfamily, traffics to the plasma membrane much more efficiently in oocytes than in HEK cells (5,38). Second, certain HCN2 trafficking mutants that do not express functionally in mammalian cells (33,35) do so in oocytes (49). For comparison, we also expressed mHCN2-N380Q or wild-type mHCN2 in CHO cells.…”
Section: Hcn2 Channels Undergo N-glycosylation In Native Cardiacmentioning
confidence: 99%
“…Together these data suggested that the doublet represented the GFP-HCN2 channel. Previous studies on HCN2 channels expressed in Hek cells showed that the doublet represented two forms of the HCN2 channel (Much et al, 2003; Akhavan et al, 2005; Nazzari et al, 2008). The slower migrating band contained a complex N -glycosylation.…”
Section: Resultsmentioning
confidence: 99%
“…The faster migrating band instead possessed a simple or no glycosylation. Complex N -glycosylation increased the efficiency of surface expression, but channels possessing only a subset of complex N -glycosylated subunits (Akhavan et al, 2005) or no complex N -glycosylated subunits (Nazzari et al, 2008) could still be detected at the plasma membrane. Relative to past studies, the doublet detected in our experiments is larger, presumably due to the GFP tag.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation